2018
DOI: 10.24874/ti.2018.40.03.01
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fibre Orientation on Tribological Performance of Jute Fibre Reinforced Epoxy Composites Considering Different Mat Orientations

Abstract: In this study, hand lay-up technique was used to fabricate epoxy composite based on jute fibre mates. Three different orientations wew considered in the fabrication of the composites. The characteristics of the material removal from the surface of the composite due to sliding condition was investigated. Different applied loads were considered to gain different shear force in the interface. Scanning electron microscopy was used to examine the influence of the shear force on the interaction between the fibre and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…It was observed that incorporating the jute fibers in polypropylene matrix lowered the specific wear rate by 65%. Alshammari et al [98] studied the tribological properties of jute-epoxy composites subjected to different fiber orientations. For the enhancements in surface properties, jute fibers were immersed in 6% NaOH solution for 24 hours following which they were cured in an oven for 24 hours at 40 C. Using block on ring setup, the effect of composite specimens in normal, PO and APO orientations were analyzed.…”
Section: Tribological Behaviormentioning
confidence: 99%
“…It was observed that incorporating the jute fibers in polypropylene matrix lowered the specific wear rate by 65%. Alshammari et al [98] studied the tribological properties of jute-epoxy composites subjected to different fiber orientations. For the enhancements in surface properties, jute fibers were immersed in 6% NaOH solution for 24 hours following which they were cured in an oven for 24 hours at 40 C. Using block on ring setup, the effect of composite specimens in normal, PO and APO orientations were analyzed.…”
Section: Tribological Behaviormentioning
confidence: 99%
“…Considering the fiber orientation and fiber content, as presented in Table 3, Acha et al [70] reported the compressive properties of unsaturated polyester reinforced with raw, acetone-washed, and detergent-washed jute fibers. Considering the effect of fiber orientation on the material wear performances, respect to the sliding directions, Alshammari et al [44] investigated jute/epoxy composites using block-on-ring (NFRC vs. stainless steel) configuration under dry contact conditions. The AP-O fibers showed a better film generating on the contact surface and a high shear resistance, allowing the authors to conclude that the AP-O fibers within epoxy matrix exerted a high friction coefficient (0.72 ± 0.13).…”
Section: Jute Fiber Nfrcsmentioning
confidence: 99%
“…As schematically shown in Figure 2 and clarified by many authors [40][41][42][43][44][45], with respect to the sliding direction, three fiber orientations within composites should be defined in a tribological contact: (a) Parallel orientation (P-O), (b) anti-parallel orientation (AP-O) and (c) normal orientation (N-O). Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two physical phenomena are set up when two surfaces with relative motion between them are in direct contact. However, surface roughness causes the points on the surfaces to make contact in discrete positions and this creates interfacial adhesion [5,6]. Then friction occurs when the two surfaces move in relation to one another.…”
Section: Introductionmentioning
confidence: 99%